OPTIMIZING DISTRIBUTION WAREHOUSE LOCATION DETERMINATION USING GEOGRAPHIC INFORMATION SYSTEM (GIS) AND LOCATION-ALLOCATION MODEL METHOD TO IMPROVE SUPPLY CHAIN EFFICIENCY AND CUSTOMER SERVICE LEVELS: Optimasi Penentuan Lokasi Gudang Distribusi Menggunakan Geographic Information System (GIS) dan Metode Location-Allocation Model untuk Meningkatkan Efisiensi Rantai Pasok dan Tingkat Layanan Pelanggan - Ratna Kurnia Dewi; Nufiajid Navy Abritia (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to optimize the location of distribution warehouses by integrating Geographic Information System (GIS) and the Location-Allocation Model to improve supply chain efficiency and customer service levels. The research employs a qualitative explanatory case study approach conducted in a national distribution company planning warehouse expansion. Data were collected through in-depth interviews, participatory observation, company documentation, and spatial data extraction, followed by thematic analysis and GIS-based network analysis. The findings reveal that the existing distribution system was spatially inefficient, with 38% of customers located more than 150 km from the central warehouse, contributing to high transportation costs and suboptimal delivery performance. The implementation of the integrated GIS and location-allocation model identified an optimal scenario involving the addition of one warehouse in the eastern region, resulting in a 23% reduction in total distribution distance, a significant decrease in transportation costs, and improved delivery accuracy and lead time. The study demonstrates that spatially integrated optimization models not only enhance cost efficiency but also strengthen service level performance. The integration of quantitative spatial modeling with qualitative managerial insights provides a holistic framework for strategic distribution network design in modern logistics environments.